The nature of the traditional icon and the contemporary icon/idol. Overlapping of the icon and idol in mass culture - Aguirre Martínez, Guillermo (Escritura e Imagen, 2023)
This article examines the nature of the contemporary icon/idol in relation/contrast to the traditional icon. Through a comparative study between both models, we identify aspects that enable a deeper exploration of the condition of image and subjectivity in contemporaneity. The overlap in the present era of the creative subject and the created object allows us to address how reality and ideality become so intertwined to the extent that the traditional significance of both is nullified.
Keywords: Traditional icon; contemporary icon; symbol; aura; mass culture